PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA DI SMP PGRI 01 KARANGPLOSO MALANG - Mahmilia Chontesa; Muhammad Hanief; Nur Hasan (VICRATINA, 2019)
Role is a dynamic process (status). If a person exercise his right and obligations according to this position, he carries out a role. In this study, the researcher took the title of the role of the teacher of islamic religion in forming good morals for students in SMP PGRI 01 Karangploso Malang. the role of teacher, especially the religious teacher is very necessary in the formation of good moral character when in the school environment. Good morals can be formed if there has been teaching and habituation between teacher and students. The study uses qualitative research that explains how the morals of students in school, how role the role of religious teachers in forming good morals of students, and how supporting factors and inhibitors of students in forming good morals students